2005
DOI: 10.1002/pola.20901
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of a bisphenol A based phthalonitrile resin

Abstract: A multiple aromatic ether linked phthalonitrile was synthesized and characterized. The oligomeric phthalonitrile monomer was prepared from the reaction of an excess amount of bisphenol A with 4,4′‐difluorobenzophenone in the presence of K2CO3 as the base in an N,N‐dimethylformamide/toluene solvent mixture, followed by end capping with 4‐nitrophthalonitrile in a two‐step, one‐pot reaction. The monomer properties were compared to those of the known resin 2,2‐bis[4‐(3,4‐dicyanophenoxy)phenyl]propane after being c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
205
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(208 citation statements)
references
References 19 publications
3
205
0
Order By: Relevance
“…As the only candidate to satisfy the flame standards of United States Navy (MIL-STD-2031), phthalonitrile resins have attracted increased attentions both in laboratory and industry areas, recently. However, high curing temperature (!250°C), high postcuring temperature (!375°C) and narrow processing window ("30°C) have also greatly limited their wide applications [5,6]. To solve these problems, phthalonitrile-based monomers with additional polymerisable groups such as amino, carboxyl, propargyl, oxazine, allyl, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As the only candidate to satisfy the flame standards of United States Navy (MIL-STD-2031), phthalonitrile resins have attracted increased attentions both in laboratory and industry areas, recently. However, high curing temperature (!250°C), high postcuring temperature (!375°C) and narrow processing window ("30°C) have also greatly limited their wide applications [5,6]. To solve these problems, phthalonitrile-based monomers with additional polymerisable groups such as amino, carboxyl, propargyl, oxazine, allyl, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide range of high-temperature resistant resin matrix composites, nitrile resin matrix composites, which possess excellent mechanical property, high-temperature resistance, abrasion resistance, flame resistance and high char yield, are widely applied in the preparation of new-style equipment [1][2]. Therefore, many researchers [3][4][5][6][7][8][9][10][11] have focused on their research of phthalic nitrile. Besides, a lot of researches [12][13][14][15] showed that phenol hydroxyl could improve the self-catalyzed property of phthalic nitrile monomer.…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in phthalonitrile polymers [1][2][3][4][5][6][7], owing to their excellent thermal and thermo-oxidative stability, high char yield, good chemical inertness, abrasion resistance, and flame resistance. But, there are several challenges to overcome with regard the processing of these materials with higher melting temperature and high processing temperature.…”
Section: Introductionmentioning
confidence: 99%